Le petit cabinet d'un amateur de ruines - Pas, Johan; Orion Art Gallery, Oostende (Oostende : Orion Art Gallery, 2002)
Casaer, Paul ; Couturier, Michel ; Deleu, Luc ; Fastenaekens, Gilbert ; Felten, Christine ; Massinger, Véronique ; Kempenaers, Jan ; Lafontaine, Marie-Jo ; Lennep, Jacques ; Op De Beeck, Hans ; Pacquée, Ria ; Stappaerts, Boy ; Van Luppen, Jaymes ; et al.
Orion Art Gallery, Oostende, 9.02 - 20.05.2002
kunstcatalogus